2020
DOI: 10.3389/fneur.2020.00035
|View full text |Cite|
|
Sign up to set email alerts
|

The Detection of Retina Microvascular Density in Subclinical Aquaporin-4 Antibody Seropositive Neuromyelitis Optica Spectrum Disorders

Abstract: Purpose: To use optical coherence tomography (OCT) and OCT angiography (OCT-A) to measure changes in the retinal structure and microvasculature of patients with aquaporin-4 antibody-positive, neuromyelitis optica spectrum disorder (NMOSD) with a history of optic neuritis (NMOSD+ON) and those without it (NMOSD-ON). Methods: A total of 27 aquaporin-4 antibody-positive NMOSD patients and 31 age-and gender-matched healthy control (HC) participants were included. In 27 NMOSD patients, 19 of them had a history of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 51 publications
(42 reference statements)
6
30
0
Order By: Relevance
“…NMOSD patients and healthy controls to determine whether primary microvascular pathology presents in NMOSD and to evaluate the clinical importance of macula capillaries as a measure of neuronal status. Our data showed that the macula densities of NMOSD with and without optic neuritis were significantly reduced than that of controls which is congruent with the previous reports (Chen et al, 2020;Kwapong et al, 2018;Mansoori et al, 2017). Our report suggests that these structural and microvascular changes of the retina are structural indicators of NMOSD before the occurrence of optic neuritis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…NMOSD patients and healthy controls to determine whether primary microvascular pathology presents in NMOSD and to evaluate the clinical importance of macula capillaries as a measure of neuronal status. Our data showed that the macula densities of NMOSD with and without optic neuritis were significantly reduced than that of controls which is congruent with the previous reports (Chen et al, 2020;Kwapong et al, 2018;Mansoori et al, 2017). Our report suggests that these structural and microvascular changes of the retina are structural indicators of NMOSD before the occurrence of optic neuritis.…”
Section: Discussionsupporting
confidence: 92%
“…Recent reports (Chen et al, 2020;Huang et al, 2019) on the macula microvasculature of NMOSD patients showed significantly reduced and slightly reduced macular density and RPC density in eyes with optic neuritis and eyes without optic neuritis respectively. The authors suggested that retinal microvascular changes occur in the subclinical phase of NMOSD and microvascular damage plays a pivotal role in the pathogenesis of NMOSD.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrary to MS-ON group, the NMOSD-ON eyes had comparable SCP, DCP, and GCC parameters to controls. In the studies of Huang et al and Chen et al, the vessel density was measured only in SCP, and in NMOSD + ON and NMOSD-ON patients, they found it lower than in healthy eyes 13,16 . Kwapong et al presented that, besides the reduced density of SCP, the density of DCP was also reduced in ON and non-ON eyes 15 .…”
Section: Discussionmentioning
confidence: 92%